2004
DOI: 10.1182/blood-2003-07-2525
|View full text |Cite
|
Sign up to set email alerts
|

Loss of circulating CD27+ memory B cells and CCR4+ T cells occurring in association with elevated EBV loads in XLP patients surviving primary EBV infection

Abstract: Detailed longitudinal studies of patients with X-linked lymphoproliferative disease (XLP) may increase our understanding of the immunologic defects that contribute to the development of lymphoma and hypogammaglobulinemia in XLP. We describe progressive changes observed in immunoglobulin concentrations, lympho-cyte subsets, and Epstein-Barr virus (EBV) loads occurring in a 2-year period in a newly infected, but otherwise healthy, carrier (patient 9). We compare these findings with those observed in the patient'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 27 publications
4
48
0
1
Order By: Relevance
“…This parallels the reduced basal levels of some serum Ig isotypes observed in XLP patients prior to EBV infection (46) as well as in uninfected SAP -/-mice (15,17). However, there tended to be a further decrease in the frequency of memory B cells following EBV infection, again mirroring the progressive decline in serum Ig levels in EBV + XLP patients (1,40) and infected SAP -/-mice (17). Our results support a recent study that reported reduced numbers of total memory B cells in 2 related XLP patients during EBV infection (40).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…This parallels the reduced basal levels of some serum Ig isotypes observed in XLP patients prior to EBV infection (46) as well as in uninfected SAP -/-mice (15,17). However, there tended to be a further decrease in the frequency of memory B cells following EBV infection, again mirroring the progressive decline in serum Ig levels in EBV + XLP patients (1,40) and infected SAP -/-mice (17). Our results support a recent study that reported reduced numbers of total memory B cells in 2 related XLP patients during EBV infection (40).…”
Section: Discussionsupporting
confidence: 57%
“…However, there tended to be a further decrease in the frequency of memory B cells following EBV infection, again mirroring the progressive decline in serum Ig levels in EBV + XLP patients (1,40) and infected SAP -/-mice (17). Our results support a recent study that reported reduced numbers of total memory B cells in 2 related XLP patients during EBV infection (40). However, this study also found reduced numbers of total B cells, in contrast to our data and data published previously (36), suggesting additional factors may affect B cell numbers in this 1 family (40).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Because of the paucity of germinal center and memory B cells in SAP-deficient mice (29,32,48), both of which are preferential reservoirs of long-term latency (6), we anticipated that maintenance of long-term latency would be defective, as we had previously shown for CD40 Ϫ/Ϫ B cells within CD40 ϩ /CD40 Ϫ chimeric mice (7). However, unexpectedly, the frequencies of latency in CD19 ϩ B cells from SAP-deficient and wild-type mice between 90 and 210 dpi were remarkably comparable, with the SAP-deficient mice showing only modest reductions ranging between 1.4-and 4-fold (circles in Fig.…”
Section: Quantitative Impact Of the Sap Mutation On Long-term Latencymentioning
confidence: 99%
“…Previous genetic studies revealed that he carried a germ line G383C SH2D1A mutation, which was predicted to lead to the substitution of arginine for serine at codon 28 of SAP. 13 Prior to the current illness, patient no. 1 had been healthy.…”
Section: Study Design Patient Nomentioning
confidence: 99%